Marine sport fishing in the Municipality of São Caetano de Odivelas, Pará State, Amazon, Brazil (Research, Society and Development, 2020)
The article identifies the socioeconomic profile of sport fishermen and characterizes this production chain in the municipality of São Caetano de Odivelas, State of Pará. The research took place in July 2019, through the application of questionnaires to sport fishermen. The age of the fishermen ranged from 21 to 80 years old, 53% had completed higher education, 15% classified autonomous and businessmen, and 47% had monthly family income above four minimum wages. About 78% did not have the General Fishing Registry (GFP), 38% used a rod with a reel and had as main target species: snook (Centropomus sp.) and Acoupa weakfish (Cynoscion acoupa), that are caught mainly with natural bait. The purchase of food, fuel and lodging was carried out in the municipality itself, contributing to the circulation of capital. The region had 91 fisher guiding and 22 fishing points characterized as the main ones for the practice of the activity. It was concluded that sport fishing is an activity that effectively contributes to income generation in the municipality, mainly to the social actors involved. An adequate development policy would be important to strengthen this production chain and expand the positive impacts on the local economy.